Ethnomathematics of the Congklak Game: A Systematic Review of Mathematical Concepts and Their Implementation in Learning - Irfah, Auli; Nugraha, Yuda Satria; Damayanti, Taulia (IKIP Siliwangi, 2026)
Ethnomathematics in mathematics education seeks to bridge abstract mathematical concepts with students’ cultural experiences, thereby enhancing the relevance and meaningfulness of learning. Traditional games represent a valuable cultural resource for contextualizing mathematics, and the Indonesian game congklak is widely recognized for embedding rich mathematical ideas within its structure and gameplay. This study aims to systematically review the mathematical concepts present in the congklak game and examine their implementation in mathematics education. A qualitative systematic literature review was conducted using articles retrieved from the Google Scholar database. The search applied specific keywords related to ethnomathematics, congklak, and mathematics education, with clearly defined inclusion and exclusion criteria. Ten peer-reviewed articles published between 2019 and 2024 were selected and analyzed through data reduction, organization, and synthesis. The findings show that congklak incorporates multiple mathematical concepts, including counting and number sequencing, arithmetic operations (addition, subtraction, multiplication, and division), geometry (plane figures, solid figures, and reflection), linear equations in one variable, and basic profit-and-loss concepts. The reviewed studies also report positive effects on students’ conceptual understanding, learning motivation, engagement, and critical thinking skills. In conclusion, congklak serves as an effective ethnomathematical learning medium that supports meaningful and contextual mathematics instruction while also contributing to cultural preservation and strengthening students’ awareness of mathematics in everyday life.